2021
DOI: 10.4102/phcfm.v13i1.2830
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of professional nurses regarding factors affecting the provision of quality health care services at selected rural public clinics in the Capricorn district, Limpopo Province

Abstract: Background: Despite many initiatives made by the National Department of Health through the Minister of Health, the provision of quality health care services remains a serious challenge in South Africa, especially in public rural clinics.Aim: The study aims to determine the perceptions of professional nurses on the factors affecting the provision of quality health care services at selected public primary health care clinics in rural areas of the Capricorn District, Limpopo Province.Setting: The study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Amongst them are inadequate provision of care, materials, consumables and manpower; unsafe and unconducive environment; unequal and inequitable service; and late diagnosis and delayed treatment. These factors and others have been reported to compromise quality of health care provided [ 14 , 40 , 41 ]. These aforementioned factors buttressed deficiencies in the structure, process and outcome of care [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst them are inadequate provision of care, materials, consumables and manpower; unsafe and unconducive environment; unequal and inequitable service; and late diagnosis and delayed treatment. These factors and others have been reported to compromise quality of health care provided [ 14 , 40 , 41 ]. These aforementioned factors buttressed deficiencies in the structure, process and outcome of care [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors and others have been reported to compromise quality of health care provided [ 14 , 40 , 41 ]. These aforementioned factors buttressed deficiencies in the structure, process and outcome of care [ 40 ]. Nigeria like most African countries is facing health care service challenges such as inadequate budget allocation to health care services and human resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the shortage of staff at clinics negatively impacts patient waiting times, leading to low patient satisfaction, poor compliance with medications, and even missed appointments [23]. Furthermore, it was reported that the number of nurses at clinic facilities should be increased to reduce the increased workload caused by many programs rendered at the clinics, thereby hindering the comprehensive PHC approach from being effectively implemented [7]. The findings are supported by a study [24], indicating that nurses working in primary healthcare settings face emotional and physical stress and have excessive workloads due to the shortage of human resources.…”
Section: Discussionmentioning
confidence: 99%
“…The PHC services render 24-hour services using a call system to attend the emergency patients. Moreover, nonemergency cases also visit the clinics for consultation as nurses are always available on a 24 hours call system [7].…”
Section: Introductionmentioning
confidence: 99%